Cyclic voltammetric investigation of the 6-keto 9-17 mono methyl substitute of octadeconoic acids - Erturan, S; Yalçin, M; Tanyolaç, S (NATL INST SCIENCE COMMUNICATION, 2001)
In this study the 6-keto 9-17 mono methyl substituted octadeconoic acids have been investigated in nonaqueous media (acetonitrile) by cyclic voltammetry. Tetrabutylammonium tetrafluoraborate (TBAFB) is used as the supporting electrolyte (C16H36BF4N) The oxidation potentials are determined against Ag/AgBF4 (0.1M) reference electrode. Effects of keto and methyl substituent on the oxidation potentials have been investigated, and kinetics and the mechanisms of reaction established.
Keywords: Chemistry